THE EFFECT OF FIRM SIZE AND LEVERAGE ON FINANCIAL PERFORMANCE WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE (STUDY ON INFRASTRUCTURE, UTILITIES, AND TRANSPORTATION SECTOR SERVICE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2018-2020) - Putri, Reya Armelia; Rokhmawati, Andewi; Fitri, Fitri (Program Pascasarjana, Universitas Riau, 2022)
This study aims to examine the effect of firm size and leverage on the company's financial performance, with good corporate governance as a moderating variable. The population in this study are service companies in the infrastructure, utilities, and transportation sectors listed on the Indonesia Stock Exchange (IDX) during the 2018–2020 period, totaling 55 companies. The research method used in the study aims to test the effect of variables through hypothesis testing using quantitative data. This study uses secondary data obtained from the website www.idx.co.id and the company's annual report. The sample selection used a purposive sampling method with 165 data points from 55 companies in each period. This study uses structural equation modeling-partial least squares (SEM-PLS) to analyze the data. The results show that firm size positively and significantly affects the company's financial performance. The leverage variable has a negative and insignificant effect on the company's financial performance. Good corporate governance, as a moderating variable, negatively strengthens the relationship between firm size and the company's financial performance. Furthermore, as a moderating variable, the good corporate governance variable does not influence the moderating leverage relationship on the company's financial performance. LN total assets measure firm size; leverage is measured by the debt-to-equity ratio (DER); return measures financial performance on assets (ROA); and good corporate governance is measured using independent commissioners.